Thread Starter


Joined Sep 19, 2008
Hie people im new . Im working on a project to research of a Single Stage Amplifier . In the process ive been playing around with the formula to find V2 as shown .

a) V2 = R2
R1 + R2 * V1

V1 being the Voltage supply
V2 being Vout

Now i need to shuffle the equation substituting R1 for (x) and making (x) the subject of the formula as follows ..

V2 = R2
x + R2 * V1

Now could someone help in showing me how to find (x) stage by stage . I tried to substitute the values in the top equation a) and i got the results as follows ...

V2 = R2
R1 +R2 * V1

= 8
6 + 8 * 12

= 8
14 * 12

= 6.8Volts

Now that we know that R1 = 6volts . Soeone assist by proving this from the following equation step by step.

V2 = 8
x + 8 * 12

Find (x) and show working ..!


Joined Mar 24, 2008
The proof is in the current. Current is set by total resistance, and is easy to calculate. Once you have current then whatever is flowing through each resistor is calulated by ohms law.

Just a suggestion, keep your formulas on the same line.

For example, your original formula could be stated as follows:

V2 = (V1 R2)/(R1+R2)

This is much less confusing overall.